Comparative phenotypic analysis of "Clostridium neonatale" and Clostridium butyricum isolates from neonates. (December 2017) - Schönherr-Hellec, S.; Klein, G.; Delannoy, J.; Ferraris, L.; Friedel, I.; Rozé, J.C.; Butel, M.J.; Aires, J.
Abstract: "Clostridium neonatale" was recently described as a new species within the Cluster I of the Clostridium genus sensu stricto . In this study, we characterized "C. neonatale" isolates (n = 42) and compared their phenotypic properties with those of Clostridium butyricum (n = 26), a close related species. Strains isolated from fecal samples of healthy neonates were tested for different phenotypic characteristics. Compared to C. butyricum, "C. neonatale" showed a significant higher surface hydrophobicity ( p = 0.0047), exopolysaccharide production ( p = 0.0069), aero-tolerance ( p = 0.0222) and viability at 30 °C ( p = 0.0006). A lower swimming ability ( p = 0.0146) and tolerance against bile (0.3%) ( p = 0.0494), acid (pH 4.5) ( p < 0.0001), osmolarity (NaCl 5%, p = 0.0188) and temperature at 50 °C ( p = 0.0013) characterized "C. neonatale" strains. Our results showed that "C. neonatale" behaves very differently from C. butyricum and suggests specific responses to environmental changes. Besides it is the first study on clinical isolates for these two anaerobic members of the newborns' gut microbiota and broadens our knowledge about their phenotypic traits. Highlights: "C. neonatale" clinical isolates were analyzed for their phenotypic characteristics. "C. neonatale" behaves very differently from its closest species C. butyricum . "C. neonatale" showed specific adaptation capabilities to environmental changes. This specific properties allow "C. neonatale" gastrointestinal tract colonization.